2013
DOI: 10.1021/jf402187q
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of 4-Acetylantroquinonol B Production by Supplementation of Its Precursor during Submerged Fermentation of Antrodia cinnamomea

Abstract: The antiproliferation activity of the ethanol extract of A. cinnamomea mycelium on hepatocellular cancer cells HepG2 was found to be associated with aroma intensity of the broth during fermentation. We hypothesized that some of the volatile compounds are the precursors of the key bioactive component 4-acetylantroquinonol B of this fungus. The major volatile compounds of A. cinnamomea were identified by GC/MS, and they are oct-1-en-3-ol, linalool, methyl phenylacetate, nerolidol, γ-cadinene and 2,4,5-trimethoxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 30 publications
2
24
0
Order By: Relevance
“…6). 4-AAQB was identified as the most promising supplement for increasing the bioactivity of A. cinnamomea during cultivation (Chiang et al, 2013;Hsieh et al, 2011). However, the effects of 4-AAQB on cancer-initiating cells have not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…6). 4-AAQB was identified as the most promising supplement for increasing the bioactivity of A. cinnamomea during cultivation (Chiang et al, 2013;Hsieh et al, 2011). However, the effects of 4-AAQB on cancer-initiating cells have not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Nerolidol has a similar structure to the polyisoprene side chain of antroquinonol. Chiang et al . demonstrated a successful approach to increasing the production of 4‐acetylantroquinonol B with the addition of nerolidol.…”
Section: Discussionmentioning
confidence: 99%
“…Nerolidol has a similar structure to the polyisoprene side chain of antroquinonol. Chiang et al 46 demonstrated a successful approach to increasing the production of 4-acetylantroquinonol B with the addition of nerolidol. They speculated that, according to the mevalonate pathway, excessive nerolidol leads to the accumulation of farnesyl diphosphate, which would be transferred to hyrdroxybenzoate or trimethoxybenzaldehyde.…”
Section: Discussionmentioning
confidence: 99%
“…UQ0 upregulates the expression of S-adenosylmethionine synthetase and provides a methyl group for the biosynthesis of AQ (Hu et al, 2016 ). Moreover, UQ0 induces the biosynthesis of 4-acetyl-AQ (Chiang et al, 2013 ). The quinone ring of AQ and 4-acetyl-AQ are synthesized via the polyketide pathway (Chou et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%